2019
DOI: 10.1055/s-0039-1688461
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Approach in Surgical Staging of Endometrial Cancer

Abstract: Objective To compare laparoscopy with laparotomy for surgical staging of endometrial cancer. Methods A cohort of women with preoperative diagnosis of endometrial cancer who underwent surgical staging was retrospectively evaluated. The main study end points were: morbidity and mortality, hospital length of stay, perioperative adverse events and recurrence rate. Data analysis was performed with the software SPSS v25 (IBM Corp., Armonk, NY, USA), categorical variables using a Chi-square and Fisher tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…In EC, for which the primary treatment is the surgical approach, it is important for the elderly group to receive adequate surgical treatment with minimally invasive techniques with lesser morbidity rates that may affect long-term survival [ 21 ]. Many studies have shown that minimally invasive techniques are associated with fewer post-operative complications, shorter hospital stays and have no effect on mortality, recurrence, or survival [ 21 , 22 ]. Nevertheless, minimally invasive techniques were observed to be used less frequently in the elderly group for no specific reason [ 20 ], but this difference seemed to disappear as shown in our study with experienced teams at tertiary centers [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In EC, for which the primary treatment is the surgical approach, it is important for the elderly group to receive adequate surgical treatment with minimally invasive techniques with lesser morbidity rates that may affect long-term survival [ 21 ]. Many studies have shown that minimally invasive techniques are associated with fewer post-operative complications, shorter hospital stays and have no effect on mortality, recurrence, or survival [ 21 , 22 ]. Nevertheless, minimally invasive techniques were observed to be used less frequently in the elderly group for no specific reason [ 20 ], but this difference seemed to disappear as shown in our study with experienced teams at tertiary centers [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these are the short learning curve, the 3-dimensional vision it provides in the surgical field, the articulation of the instruments used, and the surgeon's movement without force can be considered (29). When we look at the publications comparing the TRH approach and the TAH approach in endometrial cancer surgery, although TRH has longer operation times, it is seen that it has advantages such as less blood loss, reduced transfusion needs, a decrease in complication rates, and shorter hospital stays (30). When compared in terms of lymph node numbers, it was seen that TRH with a laparoscopic approach had similar lymph numbers (31).…”
Section: Discussionmentioning
confidence: 99%
“…Il est recommandé de la réaliser par technique mini-invasive si celle-ci est techniquement possible. Même si la technicité de la laparoscopie paraît plus complexe que la laparotomie avec un risque d’exérèse ganglionnaire moindre, de nombreux articles ont validé la faisabilité et de la sûreté de la laparoscopie dans les curages: il existe moins de complications post-opératoires, la durée de séjour est plus courte et les taux de survie et de récidive sont équivalents à la laparotomie [18] , [19] , [20] , [21] , [22] , [23] . De plus, le curage lombo-aortique doit s’étendre jusqu’à la veine rénale gauche car lorsque la région lombo-aortique est atteinte, il existe un taux non négligeable de métastases au-dessus de l‘artère mésentérique inférieure (77 %) [24] , [25] .…”
Section: Discussionunclassified